Japanese kanji for beginners : the method that's helped thousands in the U.S. and Japan learn Japanese successfully - Stout, Timothy G.; Hakone, Kaori; Uchida, Kinuka (Tokyo ; Rutland, Vermont : Tuttle Publishing, 2016)
This handy book teaches you a new mnemonics-based method to read and write the 430 highest-frequency kanji characters. The accompanying CD-ROM includes an interactive game, printable flash cards, and native-speaker audio recordings of all 430 kanji and their related vocabulary.
"JLPT N5 + N4" -- cover.
CSE
Trim Education
In English and Japanese.
Keywords: Japanese language -- Self-instruction.; Japanese language -- Study and teaching -- Foreign speakers; Japanese language -- Phonology; Chinese characters -- Japan; Japanese language -- Writing; Japanese language -- Textbooks for foreign speakers -- English; Chinese characters; Japanese language; Japanese language -- Phonology; Japanese language -- Study and teaching -- Foreign speakers; Japanese language -- Writing; Japan; Self-instruction.; Textbooks -- for English speakers